Modeling of Waste Material Costs on Road Construction Projects - Waty, Mega; W. Alisjahbana, Sofia; Gondokusumo, Onnyxiforus; Sulistio, Hendrik; Hasyim, Cholil; Ikhsan Setiawan, Muhammad; Harmanto, Dani; Saleh Ahmar, Ansari (International Journal of Engineering and Technology, 2018)
Material waste is a term from the amount of waste material percentage and is one of the serious problems in the implementation of road construction project. The research objective is to calculate the average percentage of waste material in road construction projects and obtain waste material influencing profit and make a regression model of % material waste to % profit contractors. The data obtained are 158 projects in East and North Kalimantan divided into 51 road building projects and 107 road improvement projects. The percentage of waste material on road building project is B aggregate as the largest (26%) and ready mix concrete (5.3%) as the smallest. The percentage of waste material on road improvement project is B aggregate as the largest (24.2%) and ready mix concrete (6.14%) as the smallest. The influencing waste material on the road construction project is B aggregate, lean concrete and ready mix concrete with regression equation to determine the estimated % profit contractor as a function of % material waste is Y = 7.363 -0.032 X3 - 0.078 X4 - 0.066 X6. The influenced waste material on road improvement projects are cement, B aggregate, and Land Fill  with the regression equation to determine the estimated % profit of contractor as a function of % material waste is Y = 8,702- 0,037 X4-  0,054 X5- 0,044 X7.